P38 MAPK signaling pathway activation by phenyl benzoxime in SNU-306 cells causes induction of apoptosis. (January 2019) - Chen, Wei; Tan, Yanni; Zhang, Yu
Abstract: The present study was aimed to investigate and understand the mechanism of inhibitory effect of phenyl benzoxime on proliferation of SNU-306 cells. Proliferation of SNU-306 cells transfected with wild-type p53-induced phosphatase 1 (Wip1)-siRNA or treated with phenyl benzoxime was examined by 3-(4, 5-dimethythiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Induction of apoptosis was examined by flow cytometry using annexin V-fluorescein isothiocyanate/propidium iodide staining. In SNU-306 cells Wip1 mRNA and protein expression was found to be significantly ( p < 0.05) higher compared to normal cells. However, Wip1-siRNA transfection significantly ( p < 0.02) inhibited the expression of Wip1 at 60 nmol/l. The proliferation of SNU-306 cells was inhibited to 3.7% on transfection with Wip1-siRNA. Phenyl benzoxime reduced proliferation to 92.0, 75.0, 49.0, 19.0 and 4.0% at 1, 2, 4, 8 and 10 μM doses, respectively. The expression of Wip1 was significantly ( p < 0.01) suppressed in SNU-306 cells on phenyl benzoxime treatment. Phenyl benzoxime induced apoptosis in 74.73% cells at 10 μM doses compared to 1.34% in control. Treatment with phenyl benzoxime markedly increased the expression of Bax, caspase-3 and p53 and decreased Bcl-2 mRNA. Moreover, addition of SB203580 to cultures of SNU-306 cells significantly ( p < 0.01) prevented phenyl benzoxime mediated inhibition of cell proliferation. Phenyl benzoxime induces apoptosis and inhibits SNU-306 cell proliferation by silencing Wip1 expression through p38 MAPK signaling pathway activation. Therefore, phenyl benzoxime can act as an important chemotherapeutic agent for breast cancer treatment. Highlights: Wip1-siRNA transfection significantly inhibited the expression of Wip1. Proliferation of SNU-306 cells was inhibited on transfection with Wip1-siRNA. Phenyl benzoxime reduced proliferation of SNU-306 cells. The expression of Wip1 was suppressed on phenyl benzoxime treatment. Phenyl benzoxime induced apoptosis in SNU-306 cells.